2016
DOI: 10.1098/rsta.2016.0190
|View full text |Cite
|
Sign up to set email alerts
|

Trace element and isotope deposition across the air–sea interface: progress and research needs

Abstract: The importance of the atmospheric deposition of biologically essential trace elements, especially iron, is widely recognized, as are the difficulties of accurately quantifying the rates of trace element wet and dry deposition and their fractional solubility. This paper summarizes some of the recent progress in this field, particularly that driven by the GEOTRACES, and other, international research programmes. The utility and limitations of models used to estimate atmospheric deposition flux, for example, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 113 publications
(168 reference statements)
1
47
0
Order By: Relevance
“…Manganese enters the open ocean through lithogenic dust deposition (Baker et al, 2016) and lateral advection from reducing sediments . Sediments along the relatively shallow (<1000 m depth) ocean margins tend to receive more organic deposition, hence by enhanced microbial decomposition are more anoxic and a stronger source of reduced Mn than deep sea sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese enters the open ocean through lithogenic dust deposition (Baker et al, 2016) and lateral advection from reducing sediments . Sediments along the relatively shallow (<1000 m depth) ocean margins tend to receive more organic deposition, hence by enhanced microbial decomposition are more anoxic and a stronger source of reduced Mn than deep sea sediments.…”
Section: Introductionmentioning
confidence: 99%
“…In regions where removal of dissolved metals by scavenging occurs at a much faster rate than transport by advection, ocean circulation is expected to contribute little to the overall uncertainty in dust deposition calculated from dissolved metal inventories [45,88]. In highly advective regimes, such as the eastern half of our study area under the influence of the North Equatorial Current [75], the dissolved metal distribution will be spatially smeared to a degree that may be quantifiable as biogeochemical modelling of dissolved trace element cycles improves.…”
Section: (I) Advection and Mixingmentioning
confidence: 99%
“…Baker et al [45] emphasize the need to use the full equation (not shown here) for bulk (wet plus dry) aerosol deposition. They also point out that 7 Be is preferentially incorporated into fine aerosols and removed by wet deposition, which may require adjustments to the bulk deposition equation in areas where wet deposition is significant.…”
Section: (A) Aerosol Depositionmentioning
confidence: 99%
See 2 more Smart Citations